PENGOLAHAN AIR LIMBAH EMULSI MINYAK-DETERJEN DENGAN PROSES ELEKTROKOAGULASI MENGGUNAKAN ELEKTRODA ALUMINIUM - Iswanto, Bambang; Silalahi, Mawar DS; Purnama, Fiqqy Dwinarizki (Jurnal Teknologi Lingkungan Universitas Trisakti, 2009)
Wastewater Treatment for Detergen-Oil Emulsion with Electrocoagulation Process using Aluminium Electrode. Household waste water consists mainly of oil and detergent which can give a bad impact for the environment, hard elaborated by microorganisms. This research executed with the waste treatment process electrocoagulation continuing using electrocoagulation reactor in laboratory scale. In this process is used to increase the concentration of NaCl Dissolved Aluminium decomposition, variation detergent 10 mg/L, 30 mg/L and 50 mg/L with 1 ml of oil comparison, variations in the concentration of NaCl used was 0 g/L, 0.5 gr / L, 1 g / L and the variation of time to stay 45 seconds, 55 seconds, 60 seconds and variations rapid mixing 150 rpm, 180 rpm, 200 rpm. Rapid mixing in floculation unit is 20 rpm with a settling time for 2 hours. In the research results obtained with the optimum operating conditions the concentration of NaCl 0.5 gr/L, rapid mixing of 150 rpm and detention time 45 seconds, with detergen concentration 10 mg/L COD was 92.68%, BOD 83.60%, TSS 93.52%, Detergent 99.29 %, Oil and Grease 94.55%, TKN 90.40%, VSS 93.49%,Total Phosphat 88.92%, Turbidity 98.43%, Dissolved Aluminium 0,02 mg / L. From optimum condition which in obtaining upper to be applicable in domestic sewage.